Competitive foreclosure. (13th November 2017) - Burguet, Roberto; Sákovics, József
Abstract: We model oligopolistic firms, producing substitutes, who compete for inputs from capacity constrained suppliers in a decentralized market. Compared to a price‐taking input market, the incentive to foreclose downstream competitors leads to higher input prices and to a higher aggregate amount of input acquired. This novel feature mitigates the output reducing effect of downstream market power and may even restore efficiency in the unique (input) market clearing equilibrium. Other equilibria, where firms coordinate on which suppliers to target, result in excess supply (involuntary unemployment, if input is labor) and even higher input prices. Our insights generalize to alternative vertical structures.